Analysing the need for the development of a robust HR analyst competency model and instrument for competency measurement - Arifin, Muhammad Aiman; Wan Jaafar, Wan Munira (Human Resource Management Academic Research Society, 2021)
HR analytics refers to the collection, combination, and analysis of HR data and the application of existing data to predict future HR functions. Over the past several years, with more organisations placing emphasis on the importance of existing data management, the demand for competent HR analysts has also increased tremendously. To measure the competence level of HR data analysts, tools such as competency models and instruments need to be developed A systematic review revealed that to date, there are still no instrument reported which can measure HR analyst competencies, thus this calls for a study towards developing a comprehensive instrument specific for members in the HR profession. This study employs quantitative research methods and data were collected through the conduct of a survey, where a questionnaire served as the main instrument. The findings, based on answers received from 15 respondents, revealed that 90% of the respondents agreed that there was a need to develop an instrument to measure the competence level of HR analysts. This paper examines the need to develop a new instrument to measure the competence level of HR analysts, namely the Ma-HRACM Instrument. This study also offered a few suggestions for future studies towards understanding the required competency elements for HR analysts.